Evaluation of qualitative characteristics of previous dentures in patients referred to Prosthetic department of Tabriz dental school during 10 years - Elnaz Moshelifard; Tahereh Ghaffari; Negin Farhangi (Tehran University of Medical Sciences, 2020)
Background and Aims: Different materials have been used to make dentures during different years. Teeth used in making dentures should have appropriate physical and mechanical features to meet the needs of masticatory functions, meanwhile having desired beauty. The aim of the present study was to determine the frequency of previous denture material and f its form and the duration of use in patients referring to the prosthesis department of Tabriz Dental School during 1385 to 1395. Materials and Methods: This cross-sectional descriptive study was performed on the basis of paraclinical examination on all cases of removable prostheses in patients referring to the department of prosthodontics of Tabriz University of Medical Sciences from 1385 to 1395. Based on the files, the percentage of frequency of previous denture type, previous denture tooth material, previous tooth form, previous time of denture using during the day and night were statistically evaluated by SPSS20 software. Results: The results of this study showed that out of 471 patients, 151 people used removable dentures. A study of previous denture material showed that the frequency of using dentures containing resin teeth with 48.3% was much higher than porcelain teeth with 13.8. Examination of the dental form showed that in 13.8%, the dental form was with a cusp, in 48.3% without a cusp and in 37.9% the type and form of the teeth were not clear (P<0.01). Evaluations showed that 24.1% of patients used their dentures only during the day and 41.4% of patients used them overnight. Conclusion: A 10-year study of patients with dentures at the Tabriz School of Dentistry documented the common use of resin teeth denture, as well as overnight use of them and the non-cusp form of denture teeth.